Dialektika Gaya Bahasa al-Quran dan Budaya Arab Pra-Islam: Sebuah Kajian Sosiologi Bahasa - Akhmad Muzakki (Islamica: Jurnal Studi Keislaman, 2007)
The linguistic style of the Quran is closely associated with the psychological state of the Arabs as well as with their overall civilization. When speaking of the truth?especially the truth that has to do with the unseen?Islam puts into consideration this psychological aspect and conveys this kind of truth in a metaphorical or symbolical language. By this, it is meant that the language of the Qur?an is a product of the dialectical process between what the Qur?an ought to say and the contextual reality. Therefore, the Qur?an must be understood in relation to the contextual reality so as to show its ardent adaptability to a given reality. The linguistic studies have thus far shown that when certain texts are read in isolation from the social constructs in which they are written as well as from their author, the texts will loose their true meaning and their communicative function. A literary work is above all a response to a social condition that takes place in a given time and space.